Hubungan antara psikopathi, psikopatologi dan estimkendiri dalam kalangan remaja perempuan - Khaidzir Hj Ismail,; Ong, Lee Lee (Journal of Faculty of Social Sciences and Humanities. Universiti Kebangsaan Malaysia, 2007)
This study aims to test the relationship between psychopathy, psychopathology, and self esteem. A total of 82 females adolescent were selected from few Secondary Schools in Malacca (average 16.3 years, age ranging from 14 to 17 years) responded to a questionnaire on Antisocial Process Screening Device, Symptoms Checklist-90-Revised and Rosenberg Self-esteem Scale. The findings showed that there are no correlation among trait psychopathy, psychopathology and self esteem ( r = -0.009, r=0.087, dan r = 0.114). Therefore, self esteem and psychopathology are not a good predictor to psychopathy trait. This study had suggested other aspects in trait psychopath such as difference in gender, peer, family and upbringing should be taken into consideration in future studies. In addition, treatment for psychopathy needs to consider subjects’ background and the use of multi dimensional approach